TYPOLOGY OF RELATIONSHIPS ON INCREASE COURSES TEACHER QUALIFICATIONS - Shtelmakh, H.B.; Shtelmakh, O.V. (Pedagogy of Higher and Secondary Education, 2008)
The authors define différent approaches to the notion of relations’ typology and ways of forming them in the process of the improvement of professional teachers’ skill.